'Foreigners are stealing our birth right': Moral panics and the discursive construction of Zimbabwean immigrants in South African media. (February 2015) - Banda, Felix; Mawadza, Aquilina
We examine 575 randomly selected articles on Zimbabwean immigrants from the South African Media (SAM) database to expose discourses of exclusion and the production of the psycho-social condition – moral panic. We use critical discourse analysis, notions of remediation and immediacy to scrutinize discourse structures and other discursive strategies designed to conceal mediation and authorial prejudices, and to make the reader 'experience' the actual content. In addition to making the anti-immigrant rhetoric appear legitimate, and the danger immediate and real, we argue that the apparent seamless content is often biased by selection and structured in such a way as to deny voice to immigrants and their advocates. Among other things, we conclude that since the readers' interpretations are filtered through lenses of subjectivities defined by communicative contexts characterized by job scarcity, poverty, crime and wanting healthcare, the news content heightens anxiety and miseducates more than it enlightens readers on migration issues. Hence there is a danger of SAM becoming unwitting conveyors of the same vices they preach against.